Synthesis and Reactivity of Quadridentate Schiff Base Chelates of Lanthanide(III) Ions - BALASUBRAMANIAN, V.; LOGANAYAGI, A.; NANTHINI, R.; RAVI, A.; KARTHIKEYAN, N.; MUTHUKUMARAN, S. (Asian Journal of Chemistry, 2010)
α-Naphthylisocyanation reactions are first conducted on Schiff base chelates of lanthanide(III) ion. The results of reaction reactivity clearly indicate that α-naphthylisocyanate attacks at the coordinated Schiff base chelates and after prototropic rearrangement forms α-naphthylamido derivatives. The results are investigated and based on spectroscopic results. The structures of the chelates are proposed.